Penerapan Prinsip Etika Agama dalam Manajemen Komunikasi Organisasi - Dhiya Abdul Hafiz; Muhammad Ilham Zibran; Ismail Mubarok (Jurnal Mahasiswa Kreatif, 2024)
This study aims to provide an explanation of management processes related to actions and activities related to communication management carried out within the organization. This method uses qualitative descriptive methodology. Literature research methods are used. With this method, authors collect data using note-taking techniques to check relevant information, such as books, literature, and other library materials. Elton Mayo's theory of human relations was used in this study. This research gives results that the management process is to carry out communication activities systematically and organized. Since organizational communication is the way all members interact with each other, the existence of an organization is determined by their interactions. As a result, communication management must be implemented to manage these interactions. However, the implementation of management in organizational communication means aligning management functions, namely planning, organizing, directing, and supervising communication with communication within the organization. This function flows from top to bottom within the organization, in the form of tasks, orders, delegation, etc., to ensure that communication goes well and organizational goals are achieved.